Low-viscosity high-fluidity LED-UV (Light Emitting Diode-Ultraviolet) curing rotary yellow ink

By using spherical cerium oxide and the three-dimensional envelope layer of surface polymer in the rotating yellow ink, the problem of insufficient wear resistance and antibacterial performance of existing inks is solved, and higher wear resistance and antibacterial effects are achieved, and the service life is extended. Improved liquidity.

CN119220125AActive Publication Date: 2024-12-31ZHONGSHAN FUREY PRINTING MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411599892.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2024-12-31
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The existing low-halogen wheel-rotating UV environmentally friendly inks have poor wear resistance and antibacterial properties and low fluidity, which affects its service life and quality.

Method used

Spherical cerium oxide is prepared by cerium nitrate, octylphenol polyoxyethylene ether and urea, and reacts it with vinyl trimethoxysilane in the modified solution to form a wear-resistant additive, and is added to the LED-UV curing rotary yellow ink, and passes Spherical cerium oxide and surface polymer three-dimensional envelope layer improve antibacterial and wear resistance.

Benefits of technology

It significantly improves the antibacterial and wear resistance of rotating yellow ink, extends the service life, maintains low viscosity and high flowability, ensuring the quality and quality of the ink.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of printing ink, in particular to low-viscosity high-fluidity LED-UV (Light Emitting Diode-Ultraviolet) curing rotary yellow ink. The low-viscosity and high-fluidity LED-UV curing rotary yellow ink is prepared from the following raw materials in percentage by weight: 10 to 15 percent of dipropylene glycol diacrylate, 8 to 10 percent of pentaerythritol triacrylate, 2 to 4 percent of fumed silica, 6 to 9 percent of wear-resistant additive, 5 to 10 percent of photoinitiator, 0.2 to 0.4 percent of polymerization inhibitor, 2 to 3 percent of dispersant, 7 to 13 percent of yellow pigment, 1.5 to 2.5 percent of wax powder and the balance of binder. The binder is formed by compounding urethane acrylate and epoxy acrylate according to the mass ratio of (2-3): 1; the rotary yellow ink provided by the invention not only has excellent antibacterial performance, prolongs the service life of the rotary yellow ink to a certain extent, but also has the advantages of wear resistance, low viscosity and high flowability, and effectively ensures the quality of the rotary yellow ink.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of printing inks, in particular to a low-viscosity and high-fluidity LED-UV curing rotary yellow ink. Background Art

[0002] Ink is a substance used to form graphic information during the printing process. Therefore, ink plays a very important role in printing. It directly determines the tone, color, clarity, etc. of the image on the printed product. In printing, it is necessary to understand the composition and classification of ink. Pigments and binders are the two main raw materials that make up ink. Rotary ink is an ink specially used for rotary printing presses (such as offset printing presses). It usually needs to have the characteristics of fast drying, high adhesion and printing speed. This ink is used for large-scale printing operations such as printing newspapers, magazines, books and packaging materials to achieve high-speed printing and mass production.

[0003] A low-halogen rotary UV environmentally friendly ink is disclosed in the patent document with application number "CN201210181605.6", which includes raw material components and contents (wt%): mixed resin 55-75%, mixed ultraviolet light initiator 5-11%, inhibitor 0.05-0.5%, dispersant 1-2%, pigment 16-45%, adhesion promoter 1-3%, anti-scratch agent wear-resistant additive 1-3%, and functional filler 3-8%. The low-halogen rotary UV environmentally friendly ink provided in this patent document has the advantages of fast curing, halogen-free, heavy metal-free, low irritation, good fluidity and good adhesion, and can be printed on a variety of substrates and rotary printing presses. However, its own wear resistance and antibacterial properties are relatively poor, and its fluidity is low, which affects its service life and quality to a certain extent. Therefore, the present invention provides a low-viscosity and high-fluidity LED-UV curing rotary yellow ink to solve the above-mentioned technical problems! Summary of the invention

[0004] The purpose of the present invention is to provide a low-viscosity and high-fluidity LED-UV curing rotary yellow ink. The rotary yellow ink provided by the present invention not only has excellent antibacterial properties, which prolongs its service life to a certain extent, but also has the advantages of wear resistance, low viscosity and high fluidity, effectively ensuring its quality.

[0005] To achieve the above object, the present invention provides the following technical solutions: A low-viscosity and high-fluidity LED-UV curing rotary yellow ink is composed of the following raw materials in percentage by weight: 10-15% of propylene glycol diacrylate, 8-10% of pentaerythritol triacrylate, 2-4% of fumed silica, 6-9% of wear-resistant additive, 5-10% of photoinitiator, 0.2-0.4% of inhibitor, 2-3% of dispersant, 7-13% of yellow pigment, 1.5-2.5% of wax powder, and the balance is a connecting material.

[0006] Furthermore, the preparation method of the wear-resistant additive is as follows: spherical cerium oxide is uniformly dispersed in a modified liquid at 50 to 60° C. at a solid-liquid ratio of 20 to 40 g / L, and the reaction is kept warm for 3 to 5 hours under the protection of nitrogen; after the reaction is completed, sodium allyl sulfonate with a mass of 1 to 2 times that of the spherical cerium oxide, 0.03 to 0.04 times that of potassium persulfate, and 0.2 to 0.3 times that of didecyl dimethyl ammonium chloride are added to the resulting components, and the mixture is mixed and stirred evenly, and the reaction is kept warm for 8 to 15 hours at a temperature of 60 to 70° C.; after the reaction is completed, the reaction product is separated from the solid and liquid, and the filter cake is centrifuged and washed with anhydrous ethanol and acetone for 3 to 5 times, and then vacuum dried to constant weight, and the resultant is the wear-resistant additive.

[0007] Furthermore, the preparation method of the spherical cerium oxide is as follows: add 3% to 5% of octylphenol polyoxyethylene ether by mass to a 0.3 to 0.8 mol / L aqueous solution of cerium nitrate, add urea in a molar amount of 8 to 12 times that of cerium nitrate after mechanical stirring for 5 to 10 minutes, and ultrasonically mix to completely dissolve it; then keep the obtained mixed components at a temperature of 90 to 110° C. for reaction for 10 to 15 hours; after the reaction is completed, naturally cool the obtained product components to room temperature, and after centrifugal separation, wash the obtained filter cake alternately with deionized water and anhydrous ethanol for 3 to 5 times; the washed filter cake is dried at a temperature of 60 to 90° C., and then calcined at a temperature of 400 to 500° C. for 3 to 5 hours to obtain spherical cerium oxide.

[0008] Furthermore, the preparation method of the modified liquid is: dissolving vinyltrimethoxysilane in an ethanol aqueous solution with a volume concentration of 60-75% at a dosage ratio of 0.1-0.2 g / mL, adjusting the pH to 3.2-3.8, and then stirring and hydrolyzing at a temperature of 30-40°C for 2-3 hours; the modified liquid is obtained after the hydrolysis is completed.

[0009] Furthermore, the photoinitiator is selected from any one of 2-isopropylthioxanthone, 4-dimethylaminobenzoic acid isooctyl ester, benzoin dimethyl ether, and 2,4-diethylthioxanthone.

[0010] Furthermore, the polymerization inhibitor is selected from any one of hydroquinone, tris(N-nitroso-N-phenylhydroxylamine)aluminum salt, and p-hydroxyanisole.

[0011] Furthermore, the dispersant is selected from any one of LubrizolSolsperse 3000, LubrizolSolsperseJ980, LubrizolSolsperse J900, and LubrizolSolsperse J928 dispersants.

[0012] Furthermore, the yellow pigment is selected from any one of Pigment Yellow 12, Pigment Yellow 13, and Pigment Yellow 14.

[0013] Furthermore, the wax powder is selected from any one of carnaba wax, paraffin wax and polyethylene wax.

[0014] Furthermore, the connecting material is compounded by polyurethane acrylate and epoxy acrylate in a mass ratio of 2 to 3:1.

[0015] Compared with the prior art, the present invention has the following beneficial effects: In the present invention, cerium nitrate, octylphenol polyoxyethylene ether and urea are used as raw materials to prepare spherical cerium oxide, and then the spherical cerium oxide is put into a modified liquid composed of vinyl trimethoxysilane and ethanol, and the spherical cerium oxide reacts chemically with the hydrolyzed vinyl trimethoxysilane, and finally the two are connected by chemical bonds. After the reaction is completed, sodium allyl sulfonate, potassium persulfate and didecyl dimethyl ammonium chloride are added to the resulting components respectively, and mixed and stirred to make didecyl dimethyl ammonium chloride uniformly dispersed and adsorbed on the surface of the spherical cerium oxide. Since the spherical cerium oxide has a large specific surface area, a large amount of didecyl dimethyl ammonium chloride is loaded on its surface, and finally a dense polymer three-dimensional envelope layer is formed on the surface of the spherical cerium oxide under the action of potassium persulfate. The existence of the three-dimensional envelope layer can have a certain binding effect on the didecyl dimethyl ammonium chloride on the surface of the spherical cerium oxide, reducing the probability of its migration. Under the synergistic cooperation of spherical cerium oxide and didecyl dimethyl ammonium chloride, the prepared wear-resistant additive has excellent antibacterial properties. Furthermore, the three-dimensional envelope layer can effectively improve the dispersion performance of the wear-resistant additive in the rotary yellow ink, making it more evenly dispersed. Since cerium oxide itself has excellent wear resistance, and the spherical structure can further improve its wear resistance, the wear resistance of the wear-resistant additive is significantly improved under the synergistic cooperation of the spherical cerium oxide and its surface polymer three-dimensional envelope layer.

[0016] In summary, the use of the wear-resistant additive prepared by the present invention as a raw material for LED-UV curing rotary yellow ink can not only effectively improve its antibacterial properties, extend its service life to a certain extent, but also significantly improve its wear resistance. In addition, the rotary yellow ink prepared by the present invention also has the advantages of low viscosity and high fluidity, which effectively guarantees its quality. DETAILED DESCRIPTION

[0017] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0018] A low-viscosity and high-fluidity LED-UV curing rotary yellow ink is composed of the following raw materials in percentage by weight: 10% of propylene glycol diacrylate, 8% of pentaerythritol triacrylate, 2% of fumed silica, 6% of wear-resistant additive, 5% of 2-isopropylthioxanthone, 0.2% of hydroquinone, 2% of LubrizolSolsperse 300 dispersant, 7% of pigment yellow 12, 1.5% of carnauba wax, and the balance is a connecting material; wherein the connecting material is compounded by polyurethane acrylate and epoxy acrylate in a mass ratio of 2:1.

[0019] The preparation method of the wear-resistant additive is as follows: spherical cerium oxide is uniformly dispersed in a modified liquid at 50°C at a solid-liquid ratio of 20g / L, and the mixture is kept warm for reaction for 3 hours under the protection of nitrogen; after the reaction is completed, sodium allyl sulfonate, 0.03 times potassium persulfate, and 0.2 times didecyl dimethyl ammonium chloride, which are 1 times the mass of the spherical cerium oxide, are added to the resulting components respectively, and the mixture is stirred evenly and kept warm for reaction at 60°C for 8 hours; after the reaction is completed, the reaction product is separated into solid and liquid, and the filter cake is centrifuged and washed 3 times with anhydrous ethanol and acetone respectively, and then vacuum dried to constant weight, and the obtained product is the wear-resistant additive.

[0020] The preparation method of the modified liquid is as follows: vinyltrimethoxysilane is dissolved in an ethanol aqueous solution with a volume concentration of 60% at a dosage ratio of 0.1 g / mL, the pH is adjusted to 3.2, and then stirred and hydrolyzed at a temperature of 30° C. for 2 hours; the modified liquid is obtained after the hydrolysis is completed.

[0021] The preparation method of spherical cerium oxide is as follows: add 3% of octylphenol polyoxyethylene ether by mass to a 0.3 mol / L aqueous solution of cerium nitrate, add urea in a molar amount 8 times that of cerium nitrate after mechanical stirring for 5 minutes, and ultrasonically mix to make it completely dissolved; then keep the obtained mixed components at a temperature of 90°C for 10 hours; after the reaction is completed, naturally cool the obtained product components to room temperature, and after centrifugal separation, wash the obtained filter cake alternately with deionized water and anhydrous ethanol for 3 times; the washed filter cake is dried at a temperature of 60°C, and then calcined at a temperature of 400°C for 3 hours to obtain spherical cerium oxide. Example 2

[0022] A low-viscosity and high-fluidity LED-UV curing rotary yellow ink is composed of the following raw materials in percentage by weight: 12% of dipropylene glycol diacrylate, 8% of pentaerythritol triacrylate, 3% of fumed silica, 8% of wear-resistant additive, 7% of 4-dimethylaminobenzoic acid isooctyl ester, 0.3% of tris(N-nitroso-N-phenylhydroxylamine) aluminum salt, 2.5% of Lubrizol Solsperse J98 dispersant, 10% of pigment yellow 13, 2.0% of paraffin, and the balance is a connecting material; wherein the connecting material is compounded by polyurethane acrylate and epoxy acrylate in a mass ratio of 3:1.

[0023] The preparation method of the wear-resistant additive is as follows: spherical cerium oxide is uniformly dispersed in a modified liquid at 55°C at a solid-liquid ratio of 30g / L, and the mixture is kept warm for reaction for 4 hours under the protection of nitrogen; after the reaction is completed, sodium allyl sulfonate twice the mass of the spherical cerium oxide, 0.03 times the mass of potassium persulfate, and 0.25 times the mass of didecyl dimethyl ammonium chloride are added to the resulting components, the mixture is stirred evenly, and the mixture is kept warm for reaction at 65°C for 12 hours; after the reaction is completed, the reaction product is separated into solid and liquid, the filter cake is centrifuged and washed 4 times with anhydrous ethanol and acetone respectively, and then vacuum dried to constant weight, and the obtained product is the wear-resistant additive.

[0024] The preparation method of the modified liquid is as follows: vinyltrimethoxysilane is dissolved in an ethanol aqueous solution with a volume concentration of 70% at a dosage ratio of 0.15 g / mL, the pH is adjusted to 3.5, and then stirred and hydrolyzed at a temperature of 35° C. for 3 hours; the modified liquid is obtained after the hydrolysis is completed.

[0025] The preparation method of spherical cerium oxide is as follows: add 4% of octylphenol polyoxyethylene ether by mass to a 0.5 mol / L aqueous solution of cerium nitrate, add urea with a molar amount 10 times that of cerium nitrate after mechanical stirring for 10 minutes, and ultrasonically mix to make it completely dissolved; then keep the obtained mixed components at a temperature of 100°C for 10 hours; after the reaction is completed, naturally cool the obtained product components to room temperature, and after centrifugal separation, wash the obtained filter cake alternately with deionized water and anhydrous ethanol for 4 times; the washed filter cake is dried at a temperature of 70°C, and then calcined at a temperature of 450°C for 4 hours to obtain spherical cerium oxide. Example 3

[0026] A low-viscosity and high-fluidity LED-UV curing rotary yellow ink is composed of the following raw materials in percentage by weight: 15% of propylene glycol diacrylate, 10% of pentaerythritol triacrylate, 4% of fumed silica, 9% of wear-resistant additive, 10% of benzoin dimethyl ether, 0.4% of p-hydroxyanisole, 3% of LubrizolSolsperse J900 dispersant, 13% of pigment yellow 14, 2.5% of polyethylene wax, and the balance is a connecting material; wherein the connecting material is compounded by polyurethane acrylate and epoxy acrylate in a mass ratio of 3:1.

[0027] The preparation method of the wear-resistant additive is as follows: spherical cerium oxide is uniformly dispersed in a modified liquid at 60°C at a solid-liquid ratio of 40g / L, and the mixture is kept warm for reaction for 5 hours under the protection of nitrogen; after the reaction is completed, sodium allyl sulfonate twice the mass of the spherical cerium oxide, 0.04 times the mass of potassium persulfate, and 0.3 times the mass of didecyl dimethyl ammonium chloride are added to the resulting components, the mixture is stirred evenly, and the mixture is kept warm for reaction at 70°C for 15 hours; after the reaction is completed, the reaction product is separated into solid and liquid, the filter cake is centrifuged and washed 5 times with anhydrous ethanol and acetone respectively, and then vacuum dried to constant weight, and the obtained product is the wear-resistant additive.

[0028] The preparation method of the modified liquid is as follows: vinyltrimethoxysilane is dissolved in an ethanol aqueous solution with a volume concentration of 75% at a dosage ratio of 0.2 g / mL, the pH is adjusted to 3.8, and then stirred and hydrolyzed at a temperature of 40° C. for 3 hours; the modified liquid is obtained after the hydrolysis is completed.

[0029] The preparation method of spherical cerium oxide is as follows: add 5% of octylphenol polyoxyethylene ether by mass to a 0.8 mol / L aqueous solution of cerium nitrate, add urea with a molar amount 12 times that of cerium nitrate after mechanical stirring for 10 minutes, and ultrasonically mix to make it completely dissolved; then keep the obtained mixed components at a temperature of 110°C for reaction for 15 hours; after the reaction is completed, naturally cool the obtained product components to room temperature, and after centrifugal separation, wash the obtained filter cake alternately with deionized water and anhydrous ethanol for 5 times; the washed filter cake is dried at a temperature of 90°C, and then calcined at a temperature of 500°C for 5 hours to obtain spherical cerium oxide.

[0030] Comparative Example 1: The main difference between this example and Example 1 is that this comparative example uses an equal amount of spherical cerium oxide to replace the wear-resistant additive.

[0031] Comparative Example 2: The main difference between this example and Example 1 is that in this comparative example, didecyl dimethyl ammonium chloride was not used in the process of preparing the wear-resistant additive.

[0032] Performance Testing

[0033] The following tests were performed on the various properties of the rotary yellow ink samples provided in Examples 1 to 3 and Comparative Examples 1 to 2: 1. Antibacterial performance test: The antibacterial performance of each group of rotating yellow ink samples was tested, where the culture medium was nutrient agar, and the bacterial species were Staphylococcus aureus, Escherichia coli and Aspergillus niger. A bacterial suspension concentration of 2.0×106mL was made respectively, and 0.5g of rotating yellow ink sample was added to the bacterial suspension. The mixture was cultured at 37°C for 24h, and the size of the inhibition zone was detected.

[0034] 2. Wear resistance test: Use arc wear resistance wiping tester to test each group of rotary yellow ink samples, and the score ranges from 1 to 5. The higher the score, the better the wear resistance.

[0035] 3. Fluidity test: Use a fluidity tester to test each group of rotary yellow ink samples.

[0036] 4. Adhesion test: Refer to GB / T13217.7-2023 "Ink Adhesion Test Method" to test the adhesion of each group of rotary yellow ink samples.

[0037] The obtained test data is recorded in the following table:

[0038] By comparing and analyzing the relevant data in the table, it can be seen that the rotary yellow ink provided by the present invention not only has excellent antibacterial properties, which prolongs its service life to a certain extent, but also has the advantages of wear resistance, low viscosity and high fluidity, which effectively guarantees its quality. This shows that the low-viscosity and high-fluidity LED-UV curing rotary yellow ink provided by the present invention has a broader market prospect and is more suitable for promotion.

[0039] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0040] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A low-viscosity, high-fluidity LED-UV curable rotary yellow ink, characterized in that: It is composed of the following raw materials in weight percentage: 10-15% propylene glycol diacrylate, 8-10% pentaerythritol triacrylate, 2-4% fumed silica, 6-9% wear-resistant additive, 5-10% photoinitiator, 0.2-0.4% inhibitor, 2-3% dispersant, 7-13% yellow pigment, 1.5-2.5% wax powder, and the balance is connecting material.

2. The low-viscosity and high-fluidity LED-UV curable rotary yellow ink according to claim 1, characterized in that: The preparation method of the wear-resistant additive is as follows: spherical cerium oxide is uniformly dispersed in a modified liquid at 50-60° C. at a solid-liquid ratio of 20-40 g / L, and the mixture is kept warm for reaction for 3-5 hours under the protection of nitrogen; after the reaction is completed, sodium allyl sulfonate, 0.03-0.04 times potassium persulfate, and 0.2-0.3 times didecyl dimethyl ammonium chloride, which are 1-2 times the mass of the spherical cerium oxide, are added to the resulting components respectively, and the mixture is mixed and stirred evenly, and the mixture is kept warm for reaction at a temperature of 60-70° C. for 8-15 hours; after the reaction is completed, the reaction product is separated into solid and liquid, and the filter cake is centrifugally washed with anhydrous ethanol and acetone for 3-5 times, and then vacuum dried to constant weight, so as to obtain the wear-resistant additive.

3. The low-viscosity and high-fluidity LED-UV curable rotary yellow ink according to claim 2, characterized in that: The preparation method of the spherical cerium oxide is as follows: add 3-5% of octylphenol polyoxyethylene ether by mass to a 0.3-0.8 mol / L aqueous cerium nitrate solution, stir mechanically for 5-10 minutes, add urea with a molar amount of 8-12 times that of the cerium nitrate, and mix ultrasonically to make it completely dissolved; then keep the obtained mixed components at a temperature of 90-110° C. for reaction for 10-15 hours; after the reaction is completed, naturally cool the obtained product components to room temperature, wash the obtained filter cake alternately with deionized water and anhydrous ethanol for 3-5 times after centrifugal separation; dry the washed filter cake at a temperature of 60-90° C., and then calcine at a temperature of 400-500° C. for 3-5 hours to obtain spherical cerium oxide.

4. The low-viscosity and high-fluidity LED-UV curable rotary yellow ink according to claim 2, characterized in that: The preparation method of the modified liquid is as follows: dissolving vinyltrimethoxysilane in an ethanol aqueous solution with a volume concentration of 60-75% at a dosage ratio of 0.1-0.2 g / mL, adjusting the pH to 3.2-3.8, and then stirring and hydrolyzing at a temperature of 30-40° C. for 2-3 hours; and obtaining the modified liquid after the hydrolysis is completed.

5. The low-viscosity and high-fluidity LED-UV curable rotary yellow ink according to claim 1, characterized in that: The photoinitiator is selected from any one of 2-isopropylthioxanthone, 4-dimethylaminobenzoic acid isooctyl ester, benzoin dimethyl ether, and 2,4-diethylthioxanthone.

6. The low-viscosity and high-fluidity LED-UV curable rotary yellow ink according to claim 1, characterized in that: The polymerization inhibitor is selected from any one of hydroquinone, tris(N-nitroso-N-phenylhydroxylamine)aluminum salt, and p-hydroxyanisole.

7. The low-viscosity and high-fluidity LED-UV curable rotary yellow ink according to claim 1, characterized in that: The dispersant is selected from any one of LubrizolSolsperse 3000, LubrizolSolsperse J980, LubrizolSolsperseJ900, and LubrizolSolsperse J928 dispersants.

8. The low-viscosity and high-fluidity LED-UV curable rotary yellow ink according to claim 1, characterized in that: The yellow pigment is selected from any one of Pigment Yellow 12, Pigment Yellow 13 and Pigment Yellow 14.

9. The low-viscosity and high-fluidity LED-UV curable rotary yellow ink according to claim 1, characterized in that: The wax powder is selected from any one of carnaba wax, paraffin wax and polyethylene wax.

10. The low-viscosity and high-fluidity LED-UV curable rotary yellow ink according to claim 1, characterized in that: The connecting material is compounded by polyurethane acrylate and epoxy acrylate in a mass ratio of 2 to 3:1.

Citation Information

Patent Citations

  • Low-halogen rotation UV (Ultraviolet) environment-friendly ink and preparation method thereof

    CN102702848A

  • LED-UV curing gravure ink and preparation method and application thereof

    CN111073386A

  • Yellow UV-LED high-speed ink-jet printing ink with high curing performance and preparation method thereof

    CN111349363A

  • Antibacterial environment-friendly latex paint

    CN117925019A

  • Environment-friendly finger painting stamp-pad ink and production process thereof

    CN117986924A